2014
DOI: 10.1017/s0007114514000567
|View full text |Cite
|
Sign up to set email alerts
|

Differential cellular uptake and metabolism of curcuminoids in monocytes/macrophages: regulatory effects on lipid accumulation

Abstract: We have previously shown that curcumin (CUR) may increase lipid accumulation in cultured human acute monocytic leukaemia cell line THP-1 monocytes/macrophages, but that tetrahydrocurcumin (THC), an in vivo metabolite of CUR, has no such effect. In the present study, we hypothesised that the different cellular uptake and/or metabolism of CUR and THC might be a possible explanation for the previously observed differences in their effects on lipid accumulation in THP-1 monocytes/macrophages. Chromatography with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…In cells and in vivo, curcumin and its reductive metabolites appear to be easily conjugated [11][12][13][14][15][16][17][18][19]. Glucuronidation is the predominating pathway of conjugation, and the glucuronide of hexahydro-curcumin is usually found as the major metabolite of curcumin in body fluids, organs and cells [24][25][26]. Interestingly, no trace of its glucuronidate and sulfate conjugates could be found after incubation with human microflora.…”
Section: Discussionmentioning
confidence: 99%
“…In cells and in vivo, curcumin and its reductive metabolites appear to be easily conjugated [11][12][13][14][15][16][17][18][19]. Glucuronidation is the predominating pathway of conjugation, and the glucuronide of hexahydro-curcumin is usually found as the major metabolite of curcumin in body fluids, organs and cells [24][25][26]. Interestingly, no trace of its glucuronidate and sulfate conjugates could be found after incubation with human microflora.…”
Section: Discussionmentioning
confidence: 99%
“…•Curcumin, but not THC, was taken up and increased lipid accumulation in monocytic cell line THP-1 [44].…”
Section: Studies Showing Curcumin To Be More Active Than Thcmentioning
confidence: 94%
“…Thus, the up-regulation of FOXO3a activity by curcumin, but not by THC, could be a mechanism to protect against oxidant-and lipid-induced damage in the inflammatory cells of the vascular system. Nakagawa et al [44] suggested that differential cellular uptake of curcumin and THC may be linked to the previously observed differences in their effects on lipid accumulation in macrophages. Indeed, the authors found that curcumin was readily taken up by the cells and slowly metabolized to hexahydrocurcumin sulfate but that uptake of THC was low; this finding correlated with increased lipid uptake of cells with curcumin but decreased lipid uptake of cells with THC.…”
Section: Anti-inflammatory Activitiesmentioning
confidence: 99%
“…Curcumin has shown a variety of potentially beneficial effects, including lower blood pressure, anti-tumor, anti-inflammatory, choleretic, antioxidant, and anti-inflammatory activities (Nakagawa et al, 2014; Seo et al, 2014; Zhang Y. et al, 2014). Notably, curcumin effectively reduces profibrotic effects in fibroblasts in vitro via the inhibition of key steps in the TGF-β signaling pathway (Smith et al, 2010).…”
Section: Introductionmentioning
confidence: 99%